PENGARUH RISIKO LITIGASI, FINANCIAL DISTRESS DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI (STUDI PADA PERUSAHAAN ASURANSI PERIODE 2020 HINGGA 2023) - Shabilla, Fickriana Nola; Wijayanti, Anita (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to examine and analyze the effect of litigation risk, financial distress, and profitability on accounting conservatism in insurance companies registered with the Financial Services Authority (OJK) for the 2020–2023 period. This research employs a quantitative approach using secondary data in the form of audited financial statements of insurance companies listed on the OJK. The research sample consists of 36 insurance companies selected using purposive sampling, resulting in 144 observations. The analytical method used is multiple linear regression analysis of panel data with E-Views version 12 software, and the selected panel regression model is the Random Effect Model (REM). The results show that litigation risk has a significant positive effect on accounting conservatism in insurance companies, while financial distress and profitability have a significant negative effect on accounting conservatism in insurance companies.